The Impact of EFL Learners’ Sociobiography on Language Learning Anxiety - Indah Sulistiawati; Abdul Haris Sunubi; Magdahalena Tjalla; Zulfah Fakhruddin; Mujahidah Mujahidah (Universitas Muhammadiyah Barru, 2025)
This study examined the effects of EFL learners' sociobiographical factors (age, gender, and multilingualism) on their language learning anxiety. The research employed a quantitative approach with comparative analysis methods to investigate how these sociobiographical variables influence anxiety levels among language learners. Data analysis through t-tests revealed statistically significant correlations between sociobiographical variables and language learning anxiety, with p-values less than 0.05. The findings provide valuable insights into the complex relationship between learners' backgrounds and their anxiety in language learning contexts. These results have important implications for developing targeted teaching strategies and support systems aimed at creating more inclusive and effective EFL learning environments. The study addresses existing gaps in the literature and offers guidance for future educational policy and practice.